Oriented structural design of MXene electrodes for lithium sulfur catalysis - Wang, Yu; Li, Jiaming; Gu, Qinhua; Liu, Zhilin; Zhang, Hengrui; Zheng, Shunri; Xu, Shichong; Tan, Kar Ban; Luo, Yaxiao; Yu, Zhaoliang; Li, Haibo; Han, Wenjuan; et al. (Elsevier, 2024)
The lithium-sulfur reaction can contribute to the chemical electrical energy conversion capacity due to the multi-level ion/electron transfer process. However, the appearance of soluble intermediate products prevents efficient electron transfer, making it impossible to achieve stable cycling and capacity contribution. Restricted catalysis provides a solution for inhibiting the shuttle of soluble lithium polysulfides. Herein, MXene aerogel with optimized channel utilization is designed as S host according to the polysulfide control strategy of localization, adsorption, and catalysis. With the help of the results of oriented channels, the polysulfide conversion process is optimized, providing a comprehensive scheme for inhibiting the shuttle effect. Lithium sulfur catalytic batteries have achieved high capacity and stable cycling. This system provides a comprehensive solution for lithium sulfur reaction catalysis and a new perspective for the functional application of MXene based lithium sulfur batteries.